ANALISIS ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SAHAM LQ45 ATAS PENGUMUMAN RESHUFFLE KEDUA KABINET PEMERINTAHAN PRESIDEN PRABOWO - Natashia Amelia Ariyani; Eny Trimeiningrum (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study investigates the Indonesian stock market's reaction to the announcement of President Prabowo's second cabinet reshuffle on September 8, 2025. He primary objective is to evaluate whether this political event influences stock price fluctuations and trading volume, thereby illustrating the market's capacity to effectively integrate new public information. Methods: Utilizing a quantitative approach, the research applies an event study methodology to identify unusual returns through the Market-Adjusted Model. One sample test is utilized to determine the significance of these non-normal returns, while A Paired Samples T-test investigates differences in TVA before and after the event. The sample of equities listed in the LQ45 Index was observed within an 11-day window comprising five trading days before and after the announcement date.Results: The analysis indicates statistically significant abnormal returns on days t+1, t+2, and t+4 post-reshuffle, demonstrating investors' responsiveness to political developments. Conversely, no statistically significant changes in trading volume activity were detected between pre- and post-event periods, suggesting that investor trading behavior remained largely unaltered despite price movements.Conclusion and Suggestion: This research underscores the transient effects of political events on financial markets and emphasizes the need for investors and policymakers to prepare for potential short-term disruptions following significant political announcements. Keywords: Abnormal Returns, Cabinet, Event Study, , Information, Trading, Reshuffle, Volume Activity,